Reduction behaviour of ferrous burden under simulated oxygen blast furnace conditions. (June 2015) - Liu, Y. L.; Wang, J. S.; Zhang, H. J.; Liu, J. Z.; She, X. F.; Xue, Q. G.
<x content-type="archive" xml:space="preserve">Abstract</x> The reduction behaviour of sinter and pellets was investigated by a programmable reduction apparatus to simulate the traditional blast furnace (TBF) and the oxygen blast furnace (OBF). The starting temperature for reduction of sinter and pellet in the OBF decreased 60 and 150°C compared with that in the TBF and, by the time the temperature reached 1100°C the reduction degree of sinter and pellet was 100.0 and 98.7% in the OBF compared to 94.0 and 83.1% in the TBF. The trends of the reduction rate of sinter and pellet were consistent in OBF and TBF. There are two peak values at about 60 and 80 min and in the OBF the third peak value of pellet emerged at 40 min. In addition, the mineral microstructures of the ferrous burden were characterised by means of SEM and the area proportion of metallic iron zone was obtained by SEM photos.